2015
DOI: 10.3109/07388551.2015.1114465
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ebola therapies based on monoclonal antibodies: current state and challenges ahead

Abstract: The 2014 Ebola outbreak, the largest recorded, took us largely unprepared, with no available vaccine or specific treatment. In this context, the World Health Organization (WHO) declared that the humanitarian use of experimental therapies against Ebola Virus (EBOV) is ethical. In particular, an experimental treatment consisting of a cocktail of three monoclonal antibodies (mAbs) produced in tobacco plants and specifically directed to the Ebola virus glycoprotein (GP) was tested in humans, apparently with good r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 118 publications
(176 reference statements)
0
26
0
Order By: Relevance
“…Pointing out that with the current technique to produce MAbs from transfected tobacco plants; in order to produce, as an example, 50 kg of MAbs to allow for the treatment of maybe 5000 individuals, the authors calculate that 150 tons of tobacco leaves would have to be transfected. This is a dimension exceeding current facilities by far; apart from the fact that the MAbs recovery process from tobacco biomass poses its own formidable technical challenges [30].…”
Section: Mabs Production Techniques and Capacitymentioning
confidence: 98%
See 4 more Smart Citations
“…Pointing out that with the current technique to produce MAbs from transfected tobacco plants; in order to produce, as an example, 50 kg of MAbs to allow for the treatment of maybe 5000 individuals, the authors calculate that 150 tons of tobacco leaves would have to be transfected. This is a dimension exceeding current facilities by far; apart from the fact that the MAbs recovery process from tobacco biomass poses its own formidable technical challenges [30].…”
Section: Mabs Production Techniques and Capacitymentioning
confidence: 98%
“…As comprehensively reviewed recently by Gonzalez-Gonzalez et al [30]; up to date, around 20 monoclonal antibodies have been identified and characterized, of which some were found promising to progress to testing in nonhuman primate models. This included KZ52, isolated from a human survivor and successful in protecting mice and guinea pigs from lethal infection, but failing to protect NHPs when administered as single antibody [13].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
See 3 more Smart Citations